Life after death the viola da gamba in Britain from Purcell to Dolmetsch - Holman, Peter 1946- (Boydell Press, 2010)
New research throws light on the history of the viol after Purcell, including its revival in the late eighteenth century through Charles Frederick Abel
Title from publisher's bibliographic system (viewed on 17 Feb 2023)
Keywords: Geschichte 1530-1910; Viola da gamba music / Great Britain / 18th century / History and criticism; Viola da gamba music / Great Britain / 19th century / History and criticism; Viola da Gamba; Viola-da-Gamba-Musik; Großbritannien